Pengembangan Booklet Crustacea Pantai Ujung Patikalo Untuk Meningkatkan Hasil Belajar Kognitif: Development of a Crustacean Booklet Based on Ujung Patikalo Beach to Improve the Cognitive Learning Outcomes - Surya Karinanta Sembiring; Widya Arwita; Fauziyah Harahap (Madrasah Tsanawiyah DDI Cilellang, 2026)
Animalia learning in high schools is still dominated by general textbooks that rarely integrate local biodiversity, resulting in limited cognitive learning outcomes. This study aimed to develop a Crustacea Booklet of Ujung Patikalo Beach as a learning resource for Animalia and to evaluate its validity, practicality, and effectiveness. This Research and Development (R&D) study employed the 4D model (define, design, develop, and disseminate). The study involved six expert validators, one biology teacher, and two Grade X classes of SMA Negeri 1 Tukka as the experimental and control groups. Data were collected through observations, interviews, questionnaires, documentation, and cognitive achievement tests. The booklet was rated highly valid by experts (87.01–91.73%) and received very positive responses from the teacher and students (91.66–99.00%). The experimental class achieved a high N-Gain score (0.71), exceeding that of the control class (0.39). The Independent Sample t-test indicated a significant difference in cognitive learning outcomes between the two groups (p < 0.05). These findings demonstrate that the developed booklet is a valid, practical, and effective local potential-based learning resource for improving students’ cognitive learning outcomes in Animalia.